Effect of Cellulose Acetate Beads on the Release of Transforming Growth Factor‐β. Issue 4 (August 2015) - Nishise, Shoichi; Abe, Yasuhiko; Nomura, Eiki; Sato, Takeshi; Sasaki, Yu; Iwano, Daisuke; Yagi, Makoto; Sakuta, Kazuhiro; Shibuya, Rika; Mizumoto, Naoko; Kanno, Nana; Ueno, Yoshiyuki
Abstract Transforming growth factor‐β (TGF‐β) is released by activated platelets and induces the differentiation of T‐helper 17 from naïve T cells. Contact between blood and cellulose acetate (CA) beads induces cytokine release, although their inflammatory effects on TGF‐β release are unclear. We aimed to clarify the effect of CA beads on the release of TGF‐β in vitro. We incubated peripheral blood with and without CA beads and measured platelets and TGF‐β. Compared with blood samples incubated without beads, the platelet count and amount of TGF‐β significantly decreased in blood samples incubated with CA beads. In conclusion, CA beads inhibited the release of TGF‐β from adsorbed platelets. The biological effects of this reduction of TGF‐β release during platelet adsorption to CA beads need further clarification.